2023
DOI: 10.1021/acs.jpcc.3c00723
|View full text |Cite
|
Sign up to set email alerts
|

Insights into High Li+/Mg2+ Separation Performance Using a PEI-Grafted Graphene Oxide Membrane

Abstract: Lithium extraction from brine or seawater using membrane technology has attracted extensive attention in recent years. Graphene oxide (GO), as one of the two-dimensional materials, has been proven as a competitive candidate for membranes. However, the GO membranes still suffer challenges for ion sieving due to the swelling in the aqueous solution. In this work, a GO–PEI membrane with positively charged channels was constructed by polyelectrolyte polyethyleneimine (PEI) molecular chain-grafted GO nanosheets. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…A schematic drawing of the GO-PEI membrane NH 4 + /Mg 2+ DD separation is presented in Figure 8. The -NH 2 in the positively charged PEI can be covalently cross-linked with the -COOH at the edge of the negatively charged GO during the impregnation process, forming a GO-PEI layer with controlled surface charge by layer self-assembly at the CEM [39]. The GO-PEI-modified layer changes the charge on the membrane surface from negative to positive (see Figure 3), granting stronger electrostatic membrane surface repulsion of highly valent cations (e.g., Ca 2+ , Mg 2+ ) [40].…”
Section: Mechanism Of Nh 4 + Ion-selective Transport In Go-pei Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…A schematic drawing of the GO-PEI membrane NH 4 + /Mg 2+ DD separation is presented in Figure 8. The -NH 2 in the positively charged PEI can be covalently cross-linked with the -COOH at the edge of the negatively charged GO during the impregnation process, forming a GO-PEI layer with controlled surface charge by layer self-assembly at the CEM [39]. The GO-PEI-modified layer changes the charge on the membrane surface from negative to positive (see Figure 3), granting stronger electrostatic membrane surface repulsion of highly valent cations (e.g., Ca 2+ , Mg 2+ ) [40].…”
Section: Mechanism Of Nh 4 + Ion-selective Transport In Go-pei Membranesmentioning
confidence: 99%
“…In addition, GO can form π-metal cation conjugation with Mg 2+ and adsorb part of Mg 2+ [28], thus achieving selective retention of Mg 2+ . Wang et al [39] prepared ion-selective separation membranes using GO-PEI deposited on the surface of microfiltration membranes, performing monovalent/multivalent ion-selective separation through two-dimensional nanochannels with electrostatic repulsion and size-screening capabilities. Different from the report in the literature, the TEM observation of the sample sections (see Figure S3) revealed that the GO nanosheets were not uniformly stacked on the CEM surface to form two-dimensional nanochannels.…”
Section: Mechanism Of Nh 4 + Ion-selective Transport In Go-pei Membranesmentioning
confidence: 99%
“…Lithium has seen a constant increase in demand with the rapid promotion of electric vehicles and the vigorous development of energy storage technology worldwide. Lithium recovery from brines is relatively feasible from economic and environmental considerations, which has attracted enormous interest from researchers in recent decades. The adsorption method of extracting lithium is particularly suitable for low-lithium-grade brines with an ultrahigh Mg 2+ /Li + mass ratio that is far more than 20 because it is highly selective, simple, low cost, and environmentally friendly. Up to date, the aluminum-based lithium adsorbents, lithium/aluminum-layered double hydroxides (Li/Al-LDHs), are the first successfully industrialized adsorbents used in brines for lithium recovery, attributing to their desorption properties without solubility loss. Li/Al-LDHs are typical two-dimensional structures and consist of positively charged host layers formed by Al–O octahedra and linked by hydrogen bonds with anions and water molecules sandwiched. Lithium cations exist in the holes of the hydroxide layers composed of the Al–O octahedral without forming chemical bonds with other elements. , …”
Section: Introductionmentioning
confidence: 99%